The Influence of Transplanter and Combine Harvester Use on Working Time, Labor Requirement, and Income in Organic Red Rice (Oryza rufipogon) Farming in Singojuruh District, Banyuwangi: Pengaruh Penggunaan Transplanter dan Combine Harvester Terhadap Waktu Kerja, Jumlah Tenaga Kerja, Serta Pendapatan Pada Usaha Tani Padi Merah (Oryza rufipogon) Organik Di Kecamatan Singojuruh, Banyuwangi - Triardianto, Dimas; Rakhmadina, Casilda Aulia; Adhamatika, Adhima; Indraloka, Aldi Bahaduri (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2025)
The Singojuruh District in Banyuwangi Regency plays a pivotal role in rice cultivation, characterized by a large agricultural area and the highest levels of rice production and productivity compared to other districts. Among the various rice farming practices, organic red rice cultivation has emerged as a promising alternative due to its growing market demand and favorable selling prices for farmers. However, its productivity and profitability remain suboptimal, primarily due to the limited use of agricultural machinery such as transplanters and combine harvesters. This study aims to examine the effects of mechanization—specifically the use of transplanters and combine harvesters—on working time, labor requirements, and farmers' income in organic red rice farming in the Singojuruh District. A survey method was employed, involving farmers as respondents to assess the relative conditions, distribution patterns, and inter-variable relationships. Furthermore, an independent sample t-test was conducted to compare the variables. The findings reveal that the application of transplanters and combine harvesters significantly reduces working time and labor requirements while simultaneously increasing farmers' income in organic red rice farming.